Volksrepublik China: Unterrichtsmaterialien zur Ostasiatischen Archäologie - Wagner, Mayke (e-Forschungsberichte des DAI, 2023)
The Educational Material on East Asian Archaeology is a supplementary offer for teachers and students to be used in subjects as German language, geography, history or art. It can be used as comprehensive topic area for project weeks or single themes can be selected to deepen or practice certain aspects. Two topical booklets are available: “The Great Walls of China” (48 pages) and “The Silk Roads” (64 pages). Additionally, we provide one manual for each topic (24 and 32 pages) which contains spreadsheets and supplementary information for teachers. Digital versions of booklets and manuals are available for free download at www.bridging-eurasia.org.